Canadian inter-laboratory organically bound tritium (OBT) analysis exercise. (December 2015) - Kim, S.B.; Olfert, J.; Baglan, N.; St-Amant, N.; Carter, B.; Clark, I.; Bucur, C.
Abstract: Tritium emissions are one of the main concerns with regard to CANDU reactors and Canadian nuclear facilities. After the Fukushima accident, the Canadian Nuclear Regulatory Commission suggested that models used in risk assessment of Canadian nuclear facilities be firmly based on measured data. Procedures for measurement of tritium as HTO (tritiated water) are well established, but there are no standard methods and certified reference materials for measurement of organically bound tritium (OBT) in environmental samples. This paper describes and discusses an inter-laboratory comparison study in which OBT in three different dried environmental samples (fish, Swiss chard and potato) was measured to evaluate OBT analysis methods currently used by CANDU Owners Group (COG) members. The variations in the measured OBT activity concentrations between all laboratories were less than approximately 20%, with a total uncertainty between 11 and 17%. Based on the results using the dried samples, the current OBT analysis methods for combustion, distillation and counting are generally acceptable. However, a complete consensus OBT analysis methodology with respect to freeze-drying, rinsing, combustion, distillation and counting is required. Also, an exercise using low-level tritium samples (less than 100 Bq/L or 20 Bq/kg-fresh) would be useful in the near future to more fully evaluate the current OBT analysis methods. Highlights: An inter-laboratory OBT analysis comparison was conducted. The variations of the measured OBT activity concentrations were determined. The current OBT analysis methods are generally acceptable. A consensus OBT analysis methodology is required.